Integrative strategy of learning methods to improve academic achievement in Islamic religious education - Mukhlis Fathurrohman; Ngatmin Abbas; Edy Muslimin (At Turots: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (IRE) occupies a strategic position in shaping the character and spiritual values of students. However, the effectiveness of achieving IRE learning objectives is highly dependent on the methods employed by teachers. The use of single learning methods has proven inadequate in addressing all learning domains: cognitive, affective, and psychomotor. Therefore, an integrative strategy is required in developing combinations of relevant and contextual learning methods. This study aims to examine the influence of integrating various learning methods on student academic achievement in IRE subjects, as well as to formulate an ideal strategy for developing method combinations that can strengthen all dimensions of student competency. This research employs a qualitative approach with library research methodology, sourcing from relevant books and scientific journals. The findings indicate that the integration of methods such as lectures, discussions, demonstrations, assignments, and exemplary conduct (uswatun hasanah) can create more dynamic, effective, and long-term impactful learning. Integrative learning strategies that involve method variations within a single learning cycle have proven to enhance student engagement, deepen material comprehension, and significantly shape religious character. The implications of this research emphasize that IRE teachers need to design flexible, reflective, and transformative learning plans to support the comprehensive achievement of Islamic educational objectives.